2014
DOI: 10.1111/petr.12224
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ATG‐F dosage for induction in pediatric renal transplantation: A single‐center experience

Abstract: Rabbit antithymocyte globulin (ATG-F) is an extensively used induction agent. To our knowledge, no study to date has assessed reduced ATG-F dosage in children undergoing renal transplantation. This was a retrospective analysis of pediatric renal recipients in the Department of Kidney Transplantation, The First Affiliated Hospital of Zhengzhou University, from May 2007 to February 2013. Thirty-nine children underwent renal transplantation including 25 living related and 14 cardiac deceased donor transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Chen et al (8) compared the efficacy and safety between rabbit anti-thymocyte globulin and anti-T lymphocyte globulin in renal transplant patients receiving allografts from donors who had suffered cardiac death, and indicated a higher rate of acute rejection (19.4%) but similar 1-year graft (97%) and patient survival (100%) in those receiving ATG-F compared with those determined in the present study. Shang et al (14) indicated that the rate of acute rejection at 12 months was 15.4% but the 1-year patient and graft survival was 94.9% among recipients who received ATG-F 1.5 mg/kg daily for 4 days in combination with a standard triple immunosuppression regimen. In that study, the incidence of post-operative infection was 35.9% (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al (8) compared the efficacy and safety between rabbit anti-thymocyte globulin and anti-T lymphocyte globulin in renal transplant patients receiving allografts from donors who had suffered cardiac death, and indicated a higher rate of acute rejection (19.4%) but similar 1-year graft (97%) and patient survival (100%) in those receiving ATG-F compared with those determined in the present study. Shang et al (14) indicated that the rate of acute rejection at 12 months was 15.4% but the 1-year patient and graft survival was 94.9% among recipients who received ATG-F 1.5 mg/kg daily for 4 days in combination with a standard triple immunosuppression regimen. In that study, the incidence of post-operative infection was 35.9% (14).…”
Section: Discussionmentioning
confidence: 99%
“…Shang et al (14) indicated that the rate of acute rejection at 12 months was 15.4% but the 1-year patient and graft survival was 94.9% among recipients who received ATG-F 1.5 mg/kg daily for 4 days in combination with a standard triple immunosuppression regimen. In that study, the incidence of post-operative infection was 35.9% (14).…”
Section: Discussionmentioning
confidence: 99%